Continuous casting and rolling production process for ultrathin titanium strip coil
Through continuous casting and rolling process and optimized lubricant use, the problems of large energy consumption and low efficiency in titanium tape production are solved, and the efficient and precise production of ultra-thin titanium tape is achieved, and the mechanical properties and surface of titanium tape rolls are improved. quality.
Patent Information
- Application Number
- CN202411245447.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-01-03
AI Technical Summary
The existing titanium belt production process consumes a lot of energy, is low in efficiency, high cost and poor accuracy when producing ultra-thin titanium belts, especially ultra-thin belts with a thickness below 0.3mm are difficult to process.
Using continuous casting and rolling production process, the raw materials are first heated in a smelting furnace until they are completely melted to form a titanium alloy liquid, and then cast the casting blank in a double-belt casting machine. The residual heat of the casting blank is used for hot rolling, and then through cold rolling Processed into ultra-thin titanium tape rolls and spray lubricant before each cold rolling to reduce friction and improve accuracy.
The heating step is saved, the production efficiency is improved, the rebound of the cast billet is reduced, the dimensional accuracy is improved, and the processing wear is reduced through excellent lubricant composition and spraying amount, which improves the mechanical properties and surface quality of the titanium tape roll.
Smart Images

Figure BDA0005030550700000071 
Figure BDA0005030550700000081 
Figure BDA0005030550700000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium alloy processing, and in particular to a continuous casting and rolling production process for an ultra-thin titanium strip coil. Background Art
[0002] Titanium, as a metal material, has the advantages of high specific strength, strong corrosion resistance, good biocompatibility and non-magnetic properties, so it is widely used in aerospace, chemical industry, marine engineering, medical equipment and other fields. Titanium alloy coils are rolled from titanium and other metals. Since titanium alloy coils have the advantages of corrosion resistance and antibacterial properties, they can improve thermal conductivity and electrical conductivity, and are widely used in decoration, hydrometallurgy, power chemical industry, titanium cookware and daily necessities.
[0003] The current titanium strip production process mainly uses finished plate materials for rolling. Since titanium has high specific strength, deformation resistance and resilience, it is difficult to produce ultra-thin strips with a thickness of less than 0.3 mm. Hot rolling technology is often used in the production of ultra-thin titanium strips, which requires the plate materials to be heated multiple times, resulting in high energy consumption during production, low production efficiency, high production costs and poor production precision. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a continuous casting and rolling production process for ultra-thin titanium strip coils.
[0005] The technical solution of the present invention is: a continuous casting and rolling production process of an ultra-thin titanium strip coil, comprising the following steps: S1, placing a raw material into a melting furnace, heating the raw material at 1680-1720° C. until the raw material is completely melted, and then refining for 10-15 minutes to remove scum on the surface of the raw material to obtain a titanium alloy liquid;
[0006] S2, sending the titanium alloy liquid into a double belt casting machine, the casting thickness is 14-16 mm, and the casting blank is obtained after the casting is completed;
[0007] S3, performing 3 to 5 hot rollings on the ingot, with the deformation rate of each hot rolling being ≤50%, until the thickness of the ingot reaches 1 to 2 mm, and then performing multiple cold rollings, spraying a lubricant of 10 to 20° C. on the surface of the ingot before each cold rolling, with the deformation rate of each cold rolling being ≤35%, until the thickness of the ingot reaches 0.1 to 0.3 mm, to obtain a cast strip;
[0008] S4. After degreasing and shearing the cast strip, the strip is sent to a winder for winding to obtain an ultra-thin titanium strip coil.
[0009] Description: After the raw materials are cast into ingots in the above process, the residual heat of the ingots is used for direct hot rolling, which avoids the heating step, saves energy, and improves production efficiency. After the thickness of the ingots is reduced by hot rolling, the ingots are processed into ultra-thin titanium strip coils by cold rolling, which reduces the rebound of the ingots after processing and improves the dimensional accuracy.
[0010] Furthermore, in S1, the components of the raw materials include, by weight percentage: Al 4.0-5.2%, V 1.2-3.2%, Ni 0.6-1.2%, Cu 0.3-0.6%, Fe 1.0-2.5%, and the rest is Ti.
[0011] Description: The raw materials of the above components have good fluidity and are easy to cast, and the titanium strip coils finally produced have excellent mechanical properties and fewer internal defects.
[0012] Furthermore, in S1, the refining method is: blowing argon gas into the raw material for refining, and the amount of argon gas blown in is 3 to 4 L / min.
[0013] Note: By blowing in argon for refining, the residual gas in the raw materials can be effectively discharged to avoid high-temperature oxidation of the metal elements in the raw materials.
[0014] Furthermore, in S2, the casting speed of the double-belt casting machine is 6-8 m / min, and the cooling water temperature inside the double-belt casting machine is 20-30°C.
[0015] Note: Limiting the casting speed and cooling water temperature can ensure the cooling and forming of the billet, avoid the billet from sticking to the double-belt casting machine, and ensure production efficiency.
[0016] Furthermore, in S4, the degreasing method is: using an alkaline degreasing agent to rinse the surface of the casting strip.
[0017] Note: Alkaline degreasing agent can effectively remove the residual lubricant on the surface of the casting belt and ensure the surface quality of the casting belt.
[0018] Furthermore, in S3, the lubricant comprises the following components by weight: 10 to 16 parts of polyethylene glycol monomethyl ether, TiO 2 / CaCO 3 4-6 parts of nanoparticles, 3-5 parts of triethanolamine, 2-4 parts of sodium hexametaphosphate, 20-25 parts of sulfonated castor oil, and 80-100 parts of deionized water.
[0019] Description: The above lubricant has excellent lubrication performance, can reduce the friction between the roll and the billet, and can quickly take away the heat on the billet surface, stabilize the billet size, and TiO 2 / CaCO 3 Nanoparticles can be dispersed in the lubricant to form a nano-lubricating film on the surface of the ingot, further reducing the friction coefficient of the ingot surface, reducing the machining wear of the ingot surface, and improving the surface accuracy of the ingot.
[0020] Furthermore, the spraying amount of the lubricant is 300-450 ml / m 2 .
[0021] Note: Limiting the amount of lubricant sprayed can ensure the lubrication effect and avoid processing defects on the surface of the casting.
[0022] Furthermore, the TiO 2 / CaCO 3 The method for preparing nanoparticles comprises the following steps:
[0023] S3-1, adding tetrabutyl titanate into anhydrous ethanol, stirring for 3 to 5 minutes to obtain solution A, wherein the mass ratio of tetrabutyl titanate to anhydrous ethanol is 1:5 to 6;
[0024] S3-2, adding sodium bicarbonate into deionized water, stirring until completely dissolved, to obtain solution B, wherein the mass ratio of sodium bicarbonate to deionized water is 1:10-12;
[0025] S3-3, adding solution A into solution B in 2 to 4 equal portions, and adding acetic acid into solution B once before each addition of solution A, until all solution A is added into solution B, to obtain a mixed solution, wherein the mass ratio of solution A to solution B is 1:0.6 to 1.0, and the single addition amount of acetic acid accounts for 3 to 5% of the total mass of solution A;
[0026] S3-4, placing the mixed solution into a reactor, adding sodium dodecylbenzene sulfonate to the mixed solution, and adjusting the pH of the mixed solution to 10-12 using lime milk, then reacting the mixed solution at 120-160° C. for 16-20 hours, filtering to obtain solid particles after the reaction is completed, and the amount of sodium dodecylbenzene sulfonate added accounts for 3-4% of the total mass of the mixed solution;
[0027] S3-5, wash the solid particles with anhydrous ethanol, and dry them to obtain TiO 2 / CaCO 3 Nanoparticles.
[0028] Description: The above preparation method generates hydrophilic TiO by hydrothermal reaction of tetrabutyl titanate, sodium bicarbonate and calcium hydroxide. 2 / CaCO 3 Nanoparticles make TiO 2 / CaCO 3 Nanoparticles can be evenly dispersed in the lubricant, and the generated CaCO 3 Porous structure allows lubricants to fully penetrate TiO 2 / CaCO 3 Inside the nanoparticles, the lubricating effect of the nanolubricating film is guaranteed.
[0029] Furthermore, the mass concentration of the lime milk is 20-25%.
[0030] Note: The lime milk solution of the above mass concentration is easy to prepare, has uniform composition, is safe to use, and has low preparation cost.
[0031] The beneficial effects of the present invention are:
[0032] (1) The present invention casts the raw material into a billet and directly performs hot rolling using the residual heat of the billet, thereby avoiding the heating step, saving energy, and improving production efficiency. After reducing the thickness of the billet by hot rolling, the billet is processed into an ultra-thin titanium strip coil by cold rolling, thereby reducing the springback of the billet after processing and improving the dimensional accuracy.
[0033] (2) The lubricant of the present invention has excellent lubrication performance, can reduce the friction between the roll and the billet, and can quickly remove the heat from the billet surface, stabilize the billet size, and TiO 2 / CaCO 3 Nanoparticles can be dispersed in the lubricant to form a nano-lubricating film on the surface of the ingot, further reducing the friction coefficient of the ingot surface, reducing the machining wear of the ingot surface, and improving the surface accuracy of the ingot. DETAILED DESCRIPTION
[0034] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0035] Embodiment 1: A continuous casting and rolling production process for an ultra-thin titanium strip coil comprises the following steps:
[0036] S1. Put the raw material into a smelting furnace, heat it at 1700°C until the raw material is completely melted, and then refine it for 12 minutes to remove the scum on the surface of the raw material to obtain a titanium alloy liquid; wherein the composition of the raw material includes, by weight percentage: Al 4.6%, V 2.2%, Ni0.9%, Cu 0.4%, Fe 1.7%, and the rest is Ti; the refining method is: blowing argon gas into the raw material for refining, and the argon gas blowing amount is 3-4L / min;
[0037] S2, sending the titanium alloy liquid into a double-belt casting machine, the casting thickness is 15 mm, and a casting billet is obtained after the casting is completed; wherein the casting speed of the double-belt casting machine is 7 m / min, and the cooling water temperature inside the double-belt casting machine is 25° C.;
[0038] S3, the ingot is subjected to 4 hot rollings, with the deformation rate of each hot rolling being ≤50%, until the thickness of the ingot reaches 1.5mm, and then subjected to 5 cold rollings, with a lubricant of 15℃ sprayed on the surface of the ingot before each cold rolling, with the deformation rate of each cold rolling being ≤35%, until the thickness of the ingot reaches 0.2mm, to obtain a cast strip; wherein the spraying amount of the lubricant is 370ml / m 2 The lubricant comprises the following components by weight: 13 parts of polyethylene glycol monomethyl ether, TiO2 / CaCO 3 5 parts of nanoparticles, 4 parts of triethanolamine, 3 parts of sodium hexametaphosphate, 23 parts of sulfonated castor oil, and 90 parts of deionized water;
[0039] TiO 2 / CaCO 3 The method for preparing nanoparticles comprises the following steps:
[0040] S3-1, adding tetrabutyl titanate into anhydrous ethanol, stirring for 4 minutes to obtain solution A, the mass ratio of tetrabutyl titanate to anhydrous ethanol is: 1:5.5;
[0041] S3-2, adding sodium bicarbonate into deionized water, stirring until completely dissolved, to obtain solution B, wherein the mass ratio of sodium bicarbonate to deionized water is 1:11;
[0042] S3-3, adding solution A into solution B in three equal portions, and adding acetic acid into solution B once before each addition of solution A, until all solution A is added into solution B, to obtain a mixed solution, wherein the mass ratio of solution A to solution B is 1:0.8, and the single addition amount of acetic acid accounts for 4% of the total mass of solution A;
[0043] S3-4, placing the mixed solution into a reactor, adding sodium dodecylbenzene sulfonate to the mixed solution, and adjusting the pH of the mixed solution to 11 using lime milk with a mass concentration of 23%, then reacting the mixed solution at 140° C. for 18 hours, filtering to obtain solid particles after the reaction is completed, and the amount of sodium dodecylbenzene sulfonate added accounts for 3.5% of the total mass of the mixed solution;
[0044] S3-5, wash the solid particles with anhydrous ethanol, and dry them to obtain TiO 2 / CaCO 3 Nanoparticles;
[0045] S4. Degreasing and shearing the cast strip and sending it to a winder for winding to obtain an ultra-thin titanium strip coil; wherein the degreasing method is: rinsing the surface of the cast strip with an alkaline degreasing agent; the alkaline degreasing agent adopts a commercially available product.
[0046] Example 2: This example is basically the same as Example 1, except that the ingredients of the raw materials include, by weight percentage: Al 4.0%, V 1.2%, Ni 0.6%, Cu 0.3%, Fe 1.0%, and the rest is Ti.
[0047] Example 3: This example is basically the same as Example 1, except that the ingredients of the raw materials include, by weight percentage: Al 5.2%, V 3.2%, Ni 1.2%, Cu 0.6%, Fe 2.5%, and the rest is Ti.
[0048] Example 4: This example is basically the same as Example 1, except that the refining method is: blowing argon gas into the raw material for refining, and the argon gas blowing amount is 3L / min.
[0049] Example 5: This example is basically the same as Example 1, except that the refining method is: blowing argon gas into the raw material for refining, and the argon gas blowing amount is 4L / min.
[0050] Example 6: This example is basically the same as Example 1, except that the casting speed of the double-belt casting machine is 6 m / min.
[0051] Example 7: This example is basically the same as Example 1, except that the casting speed of the double-belt casting machine is 8 m / min.
[0052] Example 8: The ingot was hot rolled for three times until the thickness of the ingot reached 2 mm.
[0053] Example 9: The ingot was hot rolled for 5 times until the thickness of the ingot reached 1 mm.
[0054] Example 10: This example is basically the same as Example 1, except that the ingot is subjected to 4 cold rolling steps until the ingot thickness reaches 0.3 mm.
[0055] Example 11: This example is basically the same as Example 1, except that the ingot is subjected to 7 cold rolling steps until the thickness of the ingot reaches 0.1 mm.
[0056] Example 12: This example is basically the same as Example 1, except that the spraying amount of the lubricant is 300 ml / m 2 .
[0057] Example 13: This example is basically the same as Example 1, except that the spraying amount of the lubricant is 450 ml / m 2 .
[0058] Example 14: This example is basically the same as Example 1, except that the lubricant comprises the following components by weight: 10 parts of polyethylene glycol monomethyl ether, 2 / CaCO 3 4 parts of nanoparticles, 3 parts of triethanolamine, 2 parts of sodium hexametaphosphate, 20 parts of sulfonated castor oil, and 80 parts of deionized water.
[0059] Example 15: This example is basically the same as Example 1, except that the lubricant comprises the following components by weight: 16 parts of polyethylene glycol monomethyl ether, 2 / CaCO 36 parts of nanoparticles, 5 parts of triethanolamine, 4 parts of sodium hexametaphosphate, 25 parts of sulfonated castor oil, and 100 parts of deionized water.
[0060] Example 16: This example is basically the same as Example 1, except that the mass ratio of tetrabutyl titanate to anhydrous ethanol is 1:5.
[0061] Example 17: This example is basically the same as Example 1, except that the mass ratio of tetrabutyl titanate to anhydrous ethanol is 1:6.
[0062] Example 18: This example is basically the same as Example 1, except that the mass ratio of sodium bicarbonate to deionized water is 1:10.
[0063] Example 19: This example is basically the same as Example 1, except that the mass ratio of sodium bicarbonate to deionized water is 1:12.
[0064] Example 20: This example is basically the same as Example 1, except that the mass ratio of solution A to solution B is 1:0.6.
[0065] Example 21: This example is basically the same as Example 1, except that the mass ratio of solution A to solution B is 1:1.0.
[0066] Example 22: This example is basically the same as Example 1, except that solution A is added to solution B in two equal portions.
[0067] Example 23: This example is basically the same as Example 1, except that solution A is added to solution B in 4 equal portions.
[0068] Example 24: This example is basically the same as Example 1, except that the single addition amount of acetic acid accounts for 3% of the total mass of solution A.
[0069] Example 25: This example is basically the same as Example 1, except that the single addition amount of acetic acid accounts for 5% of the total mass of solution A.
[0070] Example 26: This example is basically the same as Example 1, except that the pH of the mixed solution is adjusted to 10 using lime milk.
[0071] Example 27: This example is substantially the same as Example 1, except that the pH of the mixed solution is adjusted to 12 using lime milk.
[0072] Example 28: This example is basically the same as Example 1, except that the mixed solution is reacted at 120°C for 16 hours.
[0073] Example 29: This example is basically the same as Example 1, except that the mixed solution is reacted at 160°C for 20 hours.
[0074] Comparative Example 1: Using Example 1 as a reference, the ingot was directly hot rolled to 0.3 mm.
[0075] Comparative Example 2: Using Example 1 as a reference, no lubricant was sprayed during cold rolling.
[0076] Comparative Example 3: Taking Example 1 as a reference, the TiO 2 / CaCO 3 Nanoparticle removal.
[0077] Comparative Example 4: Taking Example 1 as a reference, nano-TiO 2 and nano-CaCO 3 Mechanical mixing to replace TiO 2 / CaCO 3 Nanoparticles.
[0078] Comparative Example 5: With reference to Example 1, solution A was added to solution B all at once.
[0079] Experimental Example: In order to explore the influence of the preparation parameters of each embodiment on the performance of the titanium strip coil, the titanium strip coil prepared in each embodiment was sampled, and the performance of each sample was tested. The specific exploration is as follows:
[0080] Experimental Example 1: Investigating the influence of raw material composition on the performance of titanium strip
[0081] Using Examples 1, 2, and 3 as experimental comparisons, the performance of titanium strip coils with different raw material compositions is shown in Table 1 below:
[0082] Table 1 Titanium strip performance under different raw material compositions
[0083] Group Tensile strength / MPa Thickness deviation / mm Example 1 582 ±0.006 Example 2 476 ±0.004 Example 3 668 ±0.012
[0084] It can be seen from the data in Table 1 that compared with Examples 1, 2, and 3, as the proportion of alloy elements in the raw materials increases, the tensile strength of the titanium strip gradually increases, but the thickness deviation of the titanium strip will also gradually increase. Therefore, the appropriate raw material composition can be selected according to the use requirements.
[0085] Experimental Example 2: Investigating the effect of argon injection volume on the performance of titanium strip
[0086] Using Examples 1, 4, and 5 as experimental comparisons, the performance of the titanium strip coil under different argon injection amounts is shown in Table 2 below:
[0087] Table 2 Titanium strip performance under different argon injection rates
[0088] Group Tensile strength / MPa Thickness deviation / mm Example 1 582 ±0.006 Example 4 553 ±0.010 Example 5 534 ±0.011
[0089] It can be seen from the data in Table 2 that compared with Examples 1, 4, and 5, the titanium strip coil of Example 1 has the largest tensile strength and the smallest thickness deviation, indicating that the titanium strip coil of Example 1 has the highest strength and the best dimensional accuracy, so the argon gas injection amount selected in Example 1 is optimal.
[0090] Experimental Example 3: Investigating the effect of casting speed on the performance of titanium strip
[0091] Using Examples 1, 6, and 7 as experimental comparisons, the performance of the titanium strip coil at different casting speeds is shown in Table 3 below:
[0092] Table 3 Titanium strip coil properties at different casting speeds
[0093] Group Tensile strength / MPa Thickness deviation / mm Example 1 582 ±0.006 Example 6 586 ±0.005 Example 7 541 ±0.012
[0094] It can be seen from the data in Table 3 that: compared with Examples 1, 6, and 7, the slower the casting speed, the greater the tensile strength of the titanium strip and the smaller the thickness deviation, until the tensile strength of the titanium strip in Example 1 reaches the maximum and the thickness deviation is the minimum. However, as the casting speed continues to slow down, the tensile strength and thickness deviation of the titanium strip begin to have no obvious changes. Therefore, from the perspective of production efficiency, the casting speed selected in Example 1 is optimal.
[0095] Experimental Example 4: Investigating the influence of hot rolling parameters and cold rolling parameters on the performance of titanium strip
[0096] Using Examples 1, 8, 9, 10, 11 and Comparative Example 1 as experimental comparisons, the performance of titanium strip coils under different hot rolling parameters and cold rolling parameters is shown in Table 4 below:
[0097] Table 4 Titanium strip properties under different hot rolling parameters and cold rolling parameters
[0098]
[0099]
[0100] It can be seen from the data in Table 4 that compared with Examples 1, 8, and 9, the titanium strip coil of Example 1 has the largest tensile strength and the smallest thickness deviation, indicating that the titanium strip coil of Example 1 has the highest strength and the best dimensional accuracy, so the hot rolling parameters selected in Example 1 are optimal;
[0101] Compared with Examples 1, 10, and 11, the thicker the final thickness of the titanium strip coil, the greater the tensile strength, but the thickness deviation will also become larger, so the appropriate thickness of the titanium strip coil can be selected according to the use requirements;
[0102] Compared with comparative example 1, in Example 1, after only using the hot rolling process, the tensile strength of the titanium strip coil decreased and the thickness deviation became larger. This may be because only using the hot rolling process leads to more surface defects of the titanium strip coil. Therefore, the rolling method selected in Example 1 is the best.
[0103] Experimental Example 5: Investigating the effects of lubricant composition and spraying amount on the performance of titanium strip
[0104] Using Examples 1, 12, 13, 14, 15 and Comparative Examples 2, 3, 4 as experimental comparisons, the performance of titanium strip coils with different lubricant compositions and different spraying amounts is shown in Table 5 below:
[0105] Table 5 Titanium strip performance under different lubricant compositions and different spraying amounts
[0106] Group Tensile strength / MPa Thickness deviation / mm Example 1 582 ±0.006 Example 12 573 ±0.009 Embodiment 13 585 ±0.006 Embodiment 14 562 ±0.010 Embodiment 15 567 ±0.009 Comparative Example 2 504 ±0.023 Comparative Example 3 526 ±0.020 Comparative Example 4 539 ±0.017
[0107] It can be seen from the data in Table 5 that, compared with Examples 1, 12, and 13, as the amount of lubricant sprayed increases, the tensile strength of the titanium strip increases and the thickness deviation decreases, until the tensile strength of the titanium strip in Example 1 reaches the maximum and the thickness deviation is the minimum. As the amount of lubricant sprayed continues to increase, the tensile strength and thickness deviation of the titanium strip begin to have no obvious changes. Therefore, from a cost perspective, the lubricant spraying amount selected in Example 1 is optimal;
[0108] Compared with Examples 1, 14, and 15, the titanium strip coil of Example 1 has the largest tensile strength and the smallest thickness deviation, indicating that the titanium strip coil of Example 1 has the highest strength and the best dimensional accuracy, so the lubricant selected in Example 1 has the best lubricant composition;
[0109] Compared with Comparative Examples 2, 3, and 4, when no lubricant was used during cold rolling, the tensile strength of the titanium strip coil decreased and the thickness deviation increased significantly. 2 / CaCO 3 Nanoparticles, or using nano-TiO 2 and nano-CaCO 3 Mechanical mixing to replace TiO 2 / CaCO 3 After the nanoparticles were added, the tensile strength of the titanium strip was still lower than that of Example 1, and the thickness deviation was also significantly higher than that of Example 1, which indicated that TiO 2 / CaCO 3 Nanoparticles can effectively improve the lubricating performance of lubricants, so the lubricant selected in Example 1 is optimal.
[0110] Experimental Example 6: Investigating the effects of solution A, solution B, and mixed solution ratio on the performance of titanium strip
[0111] Using Examples 1, 16, 17, 18, 19, 20, and 21 as experimental comparisons, the performance of titanium strip coils under different ratios of solution A, solution B, and mixed solution is shown in Table 6 below:
[0112] Table 6 Titanium strip performance under different ratios of solution A, solution B and mixed solution
[0113] Group Tensile strength / MPa Thickness deviation / mm Example 1 582 ±0.006 Example 16 567 ±0.007 Embodiment 17 562 ±0.009 Embodiment 18 559 ±0.009 Embodiment 19 563 ±0.008 Embodiment 20 552 ±0.009 Embodiment 21 565 ±0.008
[0114] It can be seen from the data in Table 6 that the ratio of solution A, the ratio of solution B, and the ratio of the mixed solution will all affect the performance of the titanium strip coil. Among them, the titanium strip coil of Example 1 has the largest tensile strength and the smallest thickness deviation, indicating that the titanium strip coil of Example 1 has the highest strength and the best dimensional accuracy. Therefore, the ratios of solution A, solution B, and the mixed solution selected in Example 1 are all optimal.
[0115] Experimental Example 7: Investigating the effects of the number of times solution A is added and the amount of acetic acid added on the performance of titanium strip
[0116] Using Examples 1, 22, 23, 24, 25 and Comparative Example 5 as experimental comparisons, the performance of the titanium strip coil under different addition times of solution A and different addition amounts of acetic acid is shown in Table 7 below:
[0117] Table 7 Titanium strip performance under different addition times of solution A and different addition amounts of acetic acid
[0118]
[0119]
[0120] It can be seen from the data in Table 7 that compared with Examples 1, 22, 23, 24, and 25, the number of times solution A is added and the amount of acetic acid added will affect the performance of the titanium strip coil. Among them, the titanium strip coil of Example 1 has the largest tensile strength and the smallest thickness deviation, indicating that the titanium strip coil of Example 1 has the highest strength and the best dimensional accuracy. Therefore, the number of times solution A is added and the amount of acetic acid added selected in Example 1 are both optimal;
[0121] Compared with Comparative Example 5, after adding Solution A once, the tensile strength of the titanium strip decreased and the thickness deviation increased, which indicated that the lubricating performance of the lubricant deteriorated. This may be because Solution A was added once, which caused the tetrabutyl titanate to hydrolyze too quickly, affecting the TiO 2 / CaCO 3 Generation of nanoparticles.
[0122] Experimental Example 8: Investigating the effects of pH value of mixed solution and reaction temperature on the performance of titanium strip
[0123] Using Examples 1, 26, 27, 28, and 29 as experimental comparisons, the performance of the titanium strip coils at different pH values of the mixed solution and different reaction temperatures is shown in Table 8 below:
[0124] Table 8 Titanium strip properties at different pH values and reaction temperatures of mixed solutions
[0125] Group Tensile strength / MPa Thickness deviation / mm Example 1 582 ±0.006 Embodiment 26 549 ±0.010 Embodiment 27 561 ±0.008 Embodiment 28 566 ±0.008 Embodiment 29 553 ±0.009
[0126] It can be seen from the data in Table 8 that the pH value and reaction temperature of the mixed solution will affect the performance of the titanium strip coil. Among them, the titanium strip coil of Example 1 has the largest tensile strength and the smallest thickness deviation, which means that the titanium strip coil of Example 1 has the highest strength and the best dimensional accuracy. Therefore, the pH value and reaction temperature of the mixed solution selected in Example 1 are both optimal.
Claims
1. A continuous casting and rolling production process for ultra-thin titanium strip coils, characterized in that: The following steps are involved: S1. Put the raw materials into a smelting furnace, heat them at 1680-1720°C until the raw materials are completely melted, and then refine them for 10-15 minutes to remove the scum on the surface of the raw materials to obtain titanium alloy liquid; S2, sending the titanium alloy liquid into a double belt casting machine, the casting thickness is 14-16 mm, and the casting blank is obtained after the casting is completed; S3, performing 3 to 5 hot rollings on the ingot, with the deformation rate of each hot rolling being ≤50%, until the thickness of the ingot reaches 1 to 2 mm, and then performing multiple cold rollings, spraying a lubricant of 10 to 20° C. on the surface of the ingot before each cold rolling, with the deformation rate of each cold rolling being ≤35%, until the thickness of the ingot reaches 0.1 to 0.3 mm, to obtain a cast strip; S4. After degreasing and shearing the cast strip, it is sent to a winder for winding to obtain an ultra-thin titanium strip coil.
2. The continuous casting and rolling production process of an ultra-thin titanium strip coil according to claim 1, characterized in that: In S1, the ingredients of the raw materials include, by weight percentage: Al 4.0-5.2%, V 1.2-3.2%, Ni 0.6-1.2%, Cu 0.3-0.6%, Fe 1.0-2.5%, and the rest is Ti.
3. The continuous casting and rolling production process of an ultra-thin titanium strip coil according to claim 1, characterized in that: In S1, the refining method is: blowing argon gas into the raw material for refining, and the amount of argon gas blown in is 3 to 4 L / min.
4. The continuous casting and rolling production process of an ultra-thin titanium strip coil according to claim 1, characterized in that: In S2, the casting speed of the double-belt casting machine is 6 to 8 m / min, and the cooling water temperature inside the double-belt casting machine is 20 to 30°C.
5. The continuous casting and rolling production process of an ultra-thin titanium strip coil according to claim 1, characterized in that: In S4, the degreasing method is: using an alkaline degreasing agent to rinse the surface of the casting strip.
6. The continuous casting and rolling production process of an ultra-thin titanium strip coil according to claim 1, characterized in that: In S3, the lubricant includes the following components by weight: 10 to 16 parts of polyethylene glycol monomethyl ether, 4 to 6 parts of TiO2 / CaCO3 nanoparticles, 3 to 5 parts of triethanolamine, 2 to 4 parts of sodium hexametaphosphate, 20 to 25 parts of sulfonated castor oil, and 80 to 100 parts of deionized water.
7. The continuous casting and rolling production process of an ultra-thin titanium strip coil according to claim 6, characterized in that: The spraying amount of the lubricant is 300-450 ml / m 2 .
8. The continuous casting and rolling production process of an ultra-thin titanium strip coil according to claim 6, characterized in that: The preparation method of the TiO2 / CaCO3 nanoparticles comprises the following steps: S3-1, adding tetrabutyl titanate into anhydrous ethanol, stirring for 3 to 5 minutes to obtain solution A, wherein the mass ratio of tetrabutyl titanate to anhydrous ethanol is 1:5 to 6; S3-2, adding sodium bicarbonate into deionized water, stirring until completely dissolved, to obtain solution B, wherein the mass ratio of sodium bicarbonate to deionized water is 1:10-12; S3-3, adding solution A into solution B in 2 to 4 equal portions, and adding acetic acid into solution B once before each addition of solution A, until all solution A is added into solution B, to obtain a mixed solution, wherein the mass ratio of solution A to solution B is 1:0.6 to 1.0, and the single addition amount of acetic acid accounts for 3 to 5% of the total mass of solution A; S3-4, placing the mixed solution into a reactor, adding sodium dodecylbenzene sulfonate to the mixed solution, and adjusting the pH of the mixed solution to 10-12 using lime milk, then reacting the mixed solution at 120-160° C. for 16-20 hours, filtering to obtain solid particles after the reaction is completed, and the amount of sodium dodecylbenzene sulfonate added accounts for 3-4% of the total mass of the mixed solution; S3-5. Wash the solid particles with anhydrous ethanol and obtain TiO2 / CaCO3 nanoparticles after drying.
9. The continuous casting and rolling production process of an ultra-thin titanium strip coil according to claim 8, characterized in that: The mass concentration of the lime milk is 20-25%.
Citation Information
Patent Citations
Novel lubricating oil for mechanical processing and production process thereof
CN106978241A
Lubricating oil for engineering machinery and preparation method thereof
CN108795540A
Black phosphorene water-based lubricating liquid for titanium alloy rolling and preparation method thereof
CN112574804A
Near-alpha type high-temperature titanium alloy strip and preparation method thereof
CN114231869A
Preparation method of wide pure titanium foil coiled tape
CN114405995A
